Contact with Nature and Children's Restorative Experiences: An Eye to the Future - Collado, Silvia; Staats, Henk (Frontiers in Psychology, 2016)
This article offers an overview of what has been done until now on restorative research with children and opens up new inquires for future research. Most of the work has studied children’s exposure to nature and the restorative benefits this contact provides, focusing on the renewal of children’s psychological resources. The paper begins with an introduction to children’s current tendency toward an alienation from the natural world and sets out the objectives of the article. It is followed by four main sections. The first two sections report on what we already know in this research area, distinguishing between children with normal mental capabilities and those suffering from attention-deficit hyperactivity disorder (ADHD). The findings gathered in these sections suggest that children’s contact with nature improves their mood and their cognitive functioning, increases their social interactions and reduces ADHD symptoms. The next section describes five suggestions for future research: 1) the need for considering the relational dynamics between the child and the environment in restoration research, and the concept of constrained restoration; 2) the possibility of restorative needs arising from understimulation; 3) the importance of considering children’s social context for restoration; 4) the relationship between restoration and pro-social and pro-environmental behaviors and 5) children’s restorative environments other than nature. We close by making some final remarks about the importance of restoring daily depleted resources for children’s healthy functioning.